Strategi Pemasaran Untuk Meningkatkan Daya Saing Wisata Desa Taman Bunga Manohara Desa Purwodadi - Andhatu Achsa; Rian Destiningsih; Heni Hirawati (Universitas Islam Kadiri, 2020)
Purwodadi Village is one of the villages in Tegalrejo District, Magelang Regency. The general problems faced include uneven infrastructure development due to limited development funds, poverty rates that tend to increase, lack of education and low capacity of the community, this is stated in the 2015-2020 RPJMDes. The analytical tools used are Internal Factor Evaluation Matrix, External Factor Evaluation Matrix, Internal and External Matrix, and Quantitative Strategic Planning Matrix. The results show that the position of Taman Bunga Manohara is in quadrant V (hold and maintain). The three highest strategic priorities are: optimizing the resilience and uniqueness of Taman Bunga Manohara and strategic location to get the number of tourists of all ages which will have an impact on high income levels so as to improve the economy of the surrounding community, optimize strategic locations to obtain more tourist visits a lot, and increase the professionalism of managers evenly in order to improve the management system for the realization of Taman Bunga Manohara with a high level of visitation.